New Insights into the Antioxidant Compounds of Achenes and Sprouted Buckwheat Cultivated in the Republic of Moldova - Caterina Dumitru; Rodica Mihaela Dinica; Gabriela-Elena Bahrim; Camelia Vizireanu; Liliana Baroiu; Alina Viorica Iancu; Miruna Draganescu (Applied Sciences, 2021)
It is well known that both Fagopyrum esculentum species, buckwheat achenes and buckwheat germs, contain flavonoids, and that they can be considered functional foods. In the present study we have analyzed the total content of polyphenols (TPC) and flavonoids (TFC), as well as the antioxidant activity of buckwheat ahcenes originating from the Balti region, Republic of Moldova, and also of the buckwheat sprouts over seven days of germination. The content of phytochemicals in achenes and germinated buckwheat after three and seven days was determined by HPLC–MS analysis. Using the Folin–Ciocalteu method, we recorded an increase in TPC of 360%, and of 436% in TFC after seven days of buckwheat ahcene germination. We aimed to investigate the free radical scavenging properties of methanolic extracts from ahcenes and sprouted buckwheat. We identified and quantified flavonoids and lignans such as rutin, orientin, isoorientin, vitexin, quercetin, quercitrin, isorhamnetin, lutein, apigenin, catechins, coumestrol—which have countless beneficial effects on human health—using HPLC–MS. FTIR analysis also revealed the accumulation of phenolic compounds during germination. This is the first study on the identification and quantification of phytochemicals from buckwheat achenes and sprouts from the Balti region of the Republic of Moldova.